E-Portfolios and Digital Literacy: A Powerful Combination for English Language Learners - Subiana, Ismiati Purwaningsih; Afif, Ahma (English Language, Linguistics, and Culture International Journal, 2025)
The paper was aimed at exploring the implications of e-portfolios and Padlet on the digital literacy development of ELLs. A qualitative approach under the case study design was implemented along with the use of classroom observations, interview sessions, and documented study served as the instruments to collect the data. The findings revealed that the ELL students who implemented e-portfolios using Padlet found that the students made considerable development in their digital literacy skills. They achieved proficiency in the use of digital tools and technologies, improved their communication and cooperation abilities, gained the capacity to produce and spread content via digital platforms, and strengthened their critical thinking and reflection skills. The study indicated that e-portfolios and Padlet can be helpful tools for assisting ELLs in developing the digital literacy skills required to succeed in the 21st-century classroom. IT implied that the teachers might consider giving ELLs the chance to use e-portfolios and Padlet to advance their digital literacy.